KOMPETENSI SISWA KELAS II SLTP NEGERI 1 BATAUGA DALAM MEMAHAMI KALIMAT AKTIF DAN KALIMAT PASIF BAHASA INDONESIA - Ino, La (JURNAL TRITON PENDIDIKAN, 2016)
The paper was the results of the research regarding the level of competence or the ability to comprehend active and passive sentences on the second grade students of SMP Negeri 1 Bataugu. By using qualitative-descriptive approach, the results of the research show that the students are not thorough in studying active and passive sentences. Individually, 38 respondents (82.61%) are successful, while 8 respondents (17.39%) are fail in studying active and passive sentences. Based on the above facts, it is classically concluded that the second grade students at SMP Negeri 1 Batauga have not fully comprehended the subjects yet, since 85% of the students could not obtain grade 6.5 or above.